2020
DOI: 10.1590/1983-21252020v33n109rc
|View full text |Cite
|
Sign up to set email alerts
|

Periodicity of Exposure of Hydroponic Lettuce Plants to Nutrient Solution1

Abstract: A balanced periodicity of the nutrient solution flow is essential for better agronomic performances and low production costs in hydroponic systems. Thus, the objective of this work was to evaluate the effect of periodicity of exposure of lettuce plants to the nutrient solution in an NFT hydroponic system on the production, nutrition, and profitability of this crop. The experiment was conducted in a randomized block design with five replications. The treatments consisted of four periodicities of exposure of let… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Its consumption and commercial value have increased in recent decades due to its peculiar "slightly spicy and flavorful leaves" (Cantarella et al, 2022). In the current scenario, using the hydroponic system to grow vegetables has enabled yield gains, versatility, precocity, and, most importantly, post-harvest improvements (Dalastra et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Its consumption and commercial value have increased in recent decades due to its peculiar "slightly spicy and flavorful leaves" (Cantarella et al, 2022). In the current scenario, using the hydroponic system to grow vegetables has enabled yield gains, versatility, precocity, and, most importantly, post-harvest improvements (Dalastra et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…The fresh matter of lettuce is one of the most important traits of freshly marketable vegetables [6]. The current results showed that the shoot fresh and dry matter of hydroponic lettuce improved with increasing doses of A. brasilense when compared with non-inoculated plants (Figure 1A,C).…”
Section: Discussionmentioning
confidence: 51%
“…Its cultivation in a hydroponic system has obtained more attention for healthy and quality production in a short duration [4], using a nutrient solution and protected environments to promote nutrient use efficiency for Plants 2023, 12, 3107 2 of 15 greater plant growth, nutrient accumulation, and even yield [5]. The higher concentration of nutrients (electrical conductivity) and time of exposure to the nutrient solution can increase water use efficiency, yield, and precocity of hydroponic lettuce [6]. Despite nutrient management, inoculation with plant-growth-promoting bacteria (PGPBs) is one of the sustainable alternatives that could increase nutrient use efficiency and accumulation by plants.…”
Section: Introductionmentioning
confidence: 99%